The combination of irrigation regime and water cutoff date increases the yield and water use efficiency of castor bean (Ricinus communis L.) - Avilez, Alberto Mario Arroyo [UNESP]; Acevedo, Andres Felipe Gaona [UNESP]; Giovanelli, Luan Brioschi; Saad, João Carlos Cury [UNESP]; Galvão, Ícaro Monteiro; Zocoler, João Luis [UNESP]; Zanotto, Mauricio Dutra [UNESP] (Wiley, 2025)
Castor bean (Ricinus communis L.) is a fibrous and fast-growing plant with increasing economic importance due to its ability to generate energy and in the pharmaceutical and chemical industries. This research aimed to determine the best combination of irrigation regime and irrigation cutoff date (ICD) that maximizes grain and oil yields and water use efficiency (WUE) in the castor bean hybrid AG IMA 110204. The experiments were conducted in greenhouses in randomized blocks using subdivided plots and four replicates. The plots were allocated to five irrigation regimes based on soil water tension: 20, 30, 40, 50, and 60 kPa, corresponding to I1, I2, I3, I4, and I5, respectively. The subplots show the four ICDs: 120, 130, 140, and 150 days after sowing (DAS). The I1, I2, and I3 treatments showed the highest values and did not differ in the two cycles for the following variables: weight of 100 grains, grain yield, oil yield, WUE of the grain (WUE-grains), and WUE of the oil (WUE-oil). When the irrigation cutoff was 120 DAS, in both cycles, the water regimes I1, I2, and I3 presented the highest values and did not differ in terms of grain or oil yields or WUE-grains or WUE-oil. Higher grain and oil yields with lower water demand for castor bean were obtained with the combination of 40 kPa soil water tension to define the time of irrigation and the irrigation cutoff at 120 DAS.